Efficacy of different fungicidal spray schedules in combating apple scab severity in Uttar Pradesh Himalayas - J. KUMAR, K.P. SINGH and (Indian Phytopathology, 2002)
Five spray schedules comprising of non-systemic and systemic fungicides were evaluated against apple scab (Venturia inaequalis) in the disease prone Bhatwari fruit belt in Uttar Pradesh hills, India, over 3 consecutive growing seasons (1993-95). The fungicide tested were carbendazim, thiophanate-methyl, mancozeb, bitertanol and chlorothalonil. A pre-leaf fall urea spray was also tested. Urea applied at a concentration of 5% significantly affected V. inaequalis in overwintered leaves. All the spray schedules starting at the petal fall stage were effective in reducing primary (67.8-81.2%) and secondary (82.5-90.9%) infection on leaves and fruits. Thiophanate-methyl was the most effective in checking primary infection on 1 year growth. The variables most useful in differentiating disease incidence at various tree growth stages were infection rate (rs) and area under the scab progress curve (AUSPC).